Research of wastewater tertiary treatment - Dauknys, Regimantas; Mažeikienė, Aušra (International Conference “Environmental Engineering”, 2017)
The tertiary wastewater treatment experiment was performed on the experimental stand which was installed in a wastewater treatment plant and which consisted of three filters of the diameter of 380 mm with a non-submerged media. Biologically treated wastewater was constantly supplied to these filters. Tertiary wastewater treatment process was aggravated due to low temperature of wastewater (6 °C) and high fluctuations of load according to individual pollutants – the difference between the minimum and maximum values ranged from 3 to 10 times. The productivity of removal of pollutants according to individual contamination rates reached 8 to 43%.
Keywords: tertiary treatment; biological filtration; loading by pollutants